Adsorption of p-nitrothiophenol on mesostructured polyoxometalate–silicate–surfactant composites containing Au nanoparticles: study of surface-enhanced Raman scattering activity1. Issue 47 (27th May 2015) - Wang, Li-Ping; Kuo, Shan-Chi; Jeng, U-Ser; Lai, Ying-Huang
<x xml:space="preserve">Abstract</x> When DMAB-functionalized Au-NPs@EPSS acts as the SERS substrate, the detection sensitivity of p-NTP molecules increases by ∼6 times compared with as-synthesized Au-NPs@EPSS.